Kewenangan Lembaga Negara (Analisis Penataan Kewenangan Antar Penyelenggara Pemilihan Umum Sesuai Dengan Proposional Normatif) - Firdaus Ayu Palestina; Anifatul Kiftiyah; Fariz Ulul Abshar (Jurnal JURISTIC, 2025)
This Research with the title Authority Of State Institutions (Analysis Of Arrangement Authority General Election Organizers In Accordance Normative Proposition) examines the arrangement coordination Election Organizers according to normative proportionality. Based on Law No. 17 of 2017 concerning General Elections. This research is a type of normative or doctrinal legal research, which uses two questions, namely: invitation agreement (statute approach), and accessing history (historical approach). The source of legal material in this study was obtained from legal basis material (legislation) and secondary legal materials (opinions / interviews of related figures). The method of analysis in this study uses systematization of legal material (classification makes it easy to analyze the articles) and uses qualitative descriptive in describing the content of the legislation. The results of the study concluded, First, According to Law No. 7 of 2017 concerning General Elections, the respective authorities are as follows: KPU as Election implementers, Bawaslu as Election Implementation Supervisors, and DKPP as bodies that examine and decide complaints or report the alleged violations a code of ethics which also compensates for the decisions (checks and balances) of the performance of the KPU and Bawaslu. It's just that in practice, Election Organizers are still overlapping. This is by the author, based on a review of the data based on several factors, namely: 1) Understanding of each individual's authority, which is still lacking, 2) There is intervention and pressure from other parties, 3) There is a desire to be superior, 4) Less DKPP stated firmly in every case.